Systematical Characterization of the Cotton Di19 Gene Family and the Role of GhDi19-3 and GhDi19-4 as Two Negative Regulators in Response to Salt Stress - Lanjie Zhao; Youzhong Li; Yan Li; Wei Chen; Jinbo Yao; Shengtao Fang; Youjun Lv; Yongshan Zhang; Shouhong Zhu (MDPI AG, 2022)
Drought-induced 19 (Di19) protein is a Cys2/His2 (C2H2) type zinc-finger protein, which plays a crucial role in plant development and in response to abiotic stress. This study systematically investigated the characteristics of the GhDi19 gene family, including the member number, gene structure, chromosomal distribution, promoter cis-elements, and expression profiles. Transcriptomic analysis indicated that some GhDi19s were up-regulated under heat and salt stress. Particularly, two nuclear localized proteins, GhDi19-3 and GhDi19-4, were identified as being in potential salt stress responsive roles. GhDi19-3 and GhDi19-4 decreased sensitivity under salt stress through virus-induced gene silencing (VIGS), and showed significantly lower levels of H2O2, malondialdehyde (MDA), and peroxidase (POD) as well as significantly increased superoxide dismutase (SOD) activity. This suggested that their abilities were improved to effectively reduce the reactive oxygen species (ROS) damage. Furthermore, certain calcium signaling and abscisic acid (ABA)-responsive gene expression levels showed up- and down-regulation changes in target gene-silenced plants, suggesting that GhDi19-3 and GhDi19-4 were involved in calcium signaling and ABA signaling pathways in response to salt stress. In conclusion, GhDi19-3 and GhDi19-4, two negative transcription factors, were found to be responsive to salt stress through calcium signaling and ABA signaling pathways.